Begonia hirtella Link DI JAWA - Deden Girmansyah (Research Center for Biology-Indonesian Institute of Sciences, 2014)
Begonia hirtella Link. is one of the introduced species that naturalized and grows wild in Java. This species has very good growing ability and potentially to be invasive at new habitat. Recently, there is no information about the status, existence and distribution of this species in Java. Consequently, it need to be informed about it status, presence and distribution more clearly. Collecting data from herbarium collections, internet connection, various references and some field trips were conducted. This information can improve knowledge and awareness of people as well as assisting monitoring and controlling for introduced plant species such as Begonia hirtella in Java, Indonesia.